Kajian Terhadap Peraturan Daerah Terkait Dengan Investasi Di Kabupaten Minahasa - Mamengko, Rudolf Sam; Kasenda, Victor Demsy Denly; Tampi, Butje (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The purpose of this research is to identify regional regulations related to the realization of a conducive and sustainable investment climate in Minahasa Regency. This study is normative with a legislative and analytical approach to evaluate applicable regional regulations. The focus of the research includes analysis of policies governing business permits, management of natural resources, and incentives and legal protection for investors. The results of the study indicate that several regional regulations do not fully support a sustainable investment climate. Overlapping regulations, inconsistencies with national policies, and lack of legal certainty. The recommendation is to harmonize regulations and increase the capacity for policy implementation to strengthen investment attractiveness in this region.